COUNTRY OF ORIGIN STEREOTYPING AND CONSUMER ETHNOCENTRISM IN THE INDONESIAN AUTOMOBILE INDUSTRY - Filipus Rahmat Winata; Dahlia Darmayanti (Bina Nusantara University, 2009)
To identify consumer stereotypical image in the Indonesian automobile Industry toward three countries of origin which are Japan, Germany, and America and to measure consumer ethnocentrism and preference toward Completely Build Up (CBU) imported car and locally manufactured/assembly car. Research method will employ quantitative data collection method using two administered questionnaires with bipolar pairings evaluation via convenience sampling. Total respondents will be 300 peoples whom had purchased a new first hand passenger car in the last 24 months. Data analysis is conducted using SPSS software version 16 through descriptive analysis, independent t-test, and factor analysis. CETSCALE method will be applied to measure the consumer ethnocentrism. There is a significant difference in the each country’s product evaluation. However the differences might not be affected from country bias due to the multi attribute evaluation scheme implemented (Johansshon, 1985 and Akaah and Yaprak, 1993). In addition, differences also occur among the brand knowledgeable and less brand knowledgeable consumer and so does regarding demographics diversity although only some are significant. Consumer ethnocentrism scale enables to generate three factors from the 12 ethnocentrism variable measurers. Country of origin stereotyping does exist in the Indonesian automobile industry. Japanese car which is the market leader in the market today in term of sales has the most favorable evaluation in service and engineering, fuel economical and as providing good value for money products. While Germany car still remains as producing luxurious car which strong in performance, power, reliability, comfort, and great pride of ownership though American car is the least being evaluated. Indonesia consumer seems to be reasonably ethnocentric, CBU imported products are perceived as slightly in better quality and prestige but obviously more expensive, however Indonesia consumers are somewhat still prefer to purchase locally manufactured/assembly car.